A Randomized Pilot Study of Four Dosing Schemes of Sublingual Methazolamide in Glaucoma Patients - Tan NE; Patnaik JL; McWilliams S; Seibold LK; Kahook MY (Clinical Ophthalmology)
Nicholas E Tan, Jennifer L Patnaik, Sara McWilliams, Leonard K Seibold, Malik Y Kahook Sue-Anschutz Rodgers Eye Center at the University of Colorado, Aurora, CO, USACorrespondence: Malik Y Kahook, Sue Anschutz-Rodgers Eye Center, 1675 Aurora Court, Aurora, CO, 80045, USA, Email malik.kahook@cuanschutz.eduPurpose: To evaluate the safety and efficacy of sublingual methazolamide in patients with open-angle glaucoma (OAG) and inform future trial design.Methods: Fourteen participants (28 eyes) aged 50 to 90 years with bilateral OAG and intraocular pressure (IOP) between 18 and 35 mmHg after medication washout were included. Participants were randomized to receive either 25 mg or 50 mg of sublingual methazolamide once daily for one week, followed by twice-daily administration during the second week. The primary outcome was change in IOP from baseline to days 7 and 14. Secondary outcomes included changes in serum methazolamide levels, serum electrolytes, urine pH and electrolytes, and side effects.Results: After randomization, exclusion, and two dropouts, four patients in the 25 mg group and ten in the 50 mg group completed the study in full. Both doses of sublingual methazolamide resulted in significant reductions in IOP from the post-washout baseline at all follow-up points (all p < 0.05). Lowest mean IOPs were recorded 8 hours post-dose; after a week of daily dosing, the 25 mg and 50 mg groups achieved reductions of 6.6 mmHg (− 26.5%) and 4.2 mmHg (− 19.3%), respectively (both p < 0.001). Twice-daily dosing resulted in significantly lower morning IOPs compared to once-daily in each group (p = 0.05 for 25 mg; p = 0.003 for 50 mg). Serum methazolamide levels correlated with dose amount and frequency. Serum electrolyte levels were stable throughout, while urinary pH and urinary electrolytes fluctuated based on time since last dose. Side effects of mild headaches and/or fatigue were reported by 3 out of 14 (21.4%) participants, with no serious adverse events.Conclusion: Sublingual methazolamide demonstrated effective IOP reduction with a favorable safety profile. Twice-daily dosing may offer more sustained IOP control. These findings support further investigation into sublingual methazolamide as an alternative glaucoma treatment.Keywords: IOP, carbonic anhydrase inhibitor, pressure, compounding